FEMINISME : ANTARA OTORITER DAN OTORITATIF - Endrizal Endrizal (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
This paper is a philosophical description of women's knowledge. Does gender affect the way and what knowledge will be obtained by someone. If we follow the thesis of historical materialism of Marxism, then the answer is